Rædsler fra Ribe og omegn: Skrækhistorien som global fortælling - Clasen, Mathias (Academic Quarter | Akademisk kvarter, 2011)
In Horrors from Ribe and its environs: the horror tale as a global tale, Mathias Clasen takes as a starting point the fact that the human beings from all documented cultures spend a lot of time in fictive worlds , considering that their biological goal is to pass along their genes. According to Clasen, this suggests that art has deep roots in the human biological design. Through a reading of Teddy Vorks’ horror novel The Dike, Clasen supports Joseph Caroll’s hypothesis; that literature makes us better at surviving and reproducing, because fictive tales can make us better at understanding and navigating in both our inner as our outer landscapes.